Developing Comic of Reading Material to Enhance English Vocabulary for Young Learner at SDIT Darul Istiqamah Palangka Raya - Umi Mujiarni; Joni Bungai; Misrita (Universitas Islam Negeri Palopo, 2026)
This research aimed to develop comic-based speaking materials to improve English vocabulary mastery among young learners at SDIT Darul Istiqamah Palangka Raya. This study employed Research and Development (R&D) using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The participants were third-grade students and one English teacher. Needs analysis was conducted through observation, interviews, and curriculum review, which showed that students experienced difficulties in learning vocabulary due to limited learning materials. Therefore, a slice-of-life comic featuring familiar daily situations was developed. The product was validated by content, media, and language experts before classroom implementation. Data were collected through observations, interviews, questionnaires, vocabulary tests, documentation, and expert validation. The results indicated that the comic met the required standards of content, language, and media quality. Its implementation also increased students’ interest, participation, and vocabulary learning outcomes. Therefore, the developed comic-based speaking material is valid, practical, and effective for supporting English vocabulary learning among young learners.